(untitled) (International Journal of Environmental Sciences, 2025)
Purpose: This study aims to explore the influence of cultural, socio-economic, and environmental sustainability on sustainable tourism, with attention to the mediating role of sustainable destinations. Methodology/approach: The research sample included the provincial government, the Tourism Office, entrepreneurs in the tourism sector, and members of related organizations, using proportional sampling techniques and Structural Equation Modeling (SEM) analysis with the SmartPLS 3.0 application. Results/findings: The results showed that cultural sustainability did not have a significant influence on sustainable tourism or sustainable destinations. In contrast, socio-economic and environmental sustainability proved to have significant positive effects on both aspects. Furthermore, sustainable destinations play an important role as mediators between socio-economic and environmental sustainability and sustainable tourism. This research reveals that sustainable destination development is a key factor in achieving sustainable tourism goals, particularly in Lampung Province. Limitation: This study has not examined and considered the presence of digital technology facilities, such as online travel platforms or social media, in supporting sustainable tourism. Contribution: These findings suggest the importance of policies that focus on socio-economic and environmental sustainability, as well as the strengthening of sustainability-based tourism destination management to support the growth of an environmentally friendly and highly competitive tourism sector.